PENGARUH REALISASI ANGGARAN BELANJA PEGAWAI, BELANJA BARANG DAN JASA, BELANJA MODAL TERHADAP SELISIH PERUBAHAN ANGGARAN (Studi Pada Satuan Kerja Perangkat Daerah Kota Palu) - Utami, Athirah (Katalogis, 2017)
This aim of this research is to determine and analyze: 1) officials’ expenditure realization, goods and services expenditure, and capital expenditure on budget variances on the governmental units in palu city, 2) significant impact of officials’ expenditure, goods and services expenditure, and capital expenditure simultaneous on budget variances on the governmental units in palu city, 3) significant partial impact of officials’ expenditure on budget variances on the governmental units in palu city, 4) significant partial impact of goods and services expenditure on budget variances on the governmental units in palu city, 5) significant partial impact of capital expenditure on budget variances on the governmental units in palu city.The sampel of 25 governmental units in Palu City area is chosen through purposive sampling method. Method analysis used is  quantitative and multiple linier regressions analysis. The result show that officials’ expenditure realization, goods and services expenditure, and capital expenditure simultaneously have significant impact on budget variances on the governmental units in Palu City. Partial tests show that officials’ expenditure realization and capital expenditure has in insignificant impact on budget variances on the governmental units in Palu City. The value of coefficient determinant of 0.605 indicates that 60.5% of budget variances is impacted by officials’ expenditure realization, goods and services expenditure, and capital expenditure; while 39.5% is impacted by other variables that are not studied.